Attitudes toward gender integration in policing: A study of police cadets in China. (June 2019) - Kim, Bitna; Gerber, Jurg
Abstract: Research results in Western democracies indicate that female police officers favor performing the full range of police duties (Brown, 1997). However, the full gender integration agenda in policing has been challenged, to some extent, by research indicating that female police officers prefer partial integration or segregation in non-Western societies (Natarajan, 2008a, b; Strobl, 2008). Utilizing the recent survey data collected from three police colleges in three different provinces in China, the current study examines police cadets' attitudes toward gender integration and its predictors beyond gender. Inconsistent with previous studies, this study reveals no significant difference in attitudes toward gender integration between male and female cadets, and cluster analysis results indicate that only a small portion of police cadets support giving women specialized assignments. Both male and female cadets who perceive women as having low competence levels in policing were more likely to support gender segregation. These findings highlight the importance of gender-sensitive education, curricula, and training at the police colleges and academies.